THU0650 Early help seeking or self-management: a quantitative assessment in the context of rheumatoid arthritis. (12th June 2018) - Simons, G.; Belcher, J.; Kumar, K.; Falahee, M.; Mallen, C.D.; Stack, R.J.; Raza, K.
Abstract : Background: Rheumatoid arthritis (RA) should be treated with DMARDs in its earliest stages to reduce the likelihood of permanent joint damage and disability 1 . This therapeutic window is often missed. One important cause is delayed help seeking by patients themselves 2 . Qualitative work with members of the public has previously identified a number of potential causes for this delay 3 . Objectives: To quantify and extend the findings of existing qualitative research investigating factors which impact on speedy help seeking for symptoms of RA. Methods: A survey of members of the public without a diagnosis of inflammatory arthritis assessed the speed with which they would seek medical attention if they were to experience symptoms of RA (stiffness, pain and joint swelling). It explored factors which might impact on the speed with which help would be sought, including: self-management of symptoms; barriers to and drivers of help seeking and information seeking. Results: 1088 people (788 females; 9 undisclosed) aged between 18 and 96 years completed the survey. 48% indicated that they would seek help quickly for RA symptoms, however 63% would delay seeing their GP in order to try to self-manage the symptoms. Most intended to self-manage with over the counter medication (e.g. ibuprofen), massaging the joint or exercising. Barriers endorsed included difficulty getting a GP appointment (39%); fear of wasting the GP's time (34%) and being busy with family/work (37%). Drivers (>90%) included worsening of symptoms, inability to work, struggling to do usual activities, symptoms spreading to other parts of the body or inability to self-manage symptoms. Most participants would seek out information prior to seeking medical attention for the symptoms. Sources of information frequently endorsed were: Internet (74%); relatives/friends (49%); someone with a joint problem (41%) and pharmacists (37%). Conclusions: Less than half of the current sample would seek help quickly for the symptoms of RA. Several barriers and drivers identified in qualitative research 3 were endorsed by the survey sample making them valid targets for interventions Most participants would further seek out information about the symptoms prior to seeking medical attention and their preferred sources of information such as the internet or the pharmacist should be used in these targeted interventions. References: [1] Raza K, Filer A. The therapeutic window of opportunity in rheumatoid arthritis: does it ever close?Ann Rheum Dis2015;74:793–4. [2] Stack RJ, et al. Patient delays in seeking help at the onset of rheumatoid arthritis: the problem, its causes and potential solutions. Aging Health2013;9:425–35. [3] Simons G, et al. A qualitative investigation of the barriers to help-seeking among members of the public presented with symptoms of new-onset rheumatoid arthritis. J. Rheumatol2015;42:585–92. Acknowledgements: This research was supported by The Dunhill Medical Trust (grant number R226/1111) and the National Institute for Health Research, through the Primary Care Research Network. CDM is funded by the NIHR CLAHRC West Midlands, the NIHR School for Primary Care Research and a NIHR Research Professorship in General Practice (NIHR-RP-2014–04–026). KR is funded by the Birmingham NIHR BRC. The authors would like to thank the patient research partners who have been involved in the project. Disclosure of Interest: None declared